Impact of Emergency Remote Teaching (ERT) on Mental Health Status and Education of UniKL-RCMP Students during COVID-19 Pandemic - Nur Afiqah Mohamad Ayub; Nour Hanah Othman (Asian Journal of Medicine & Health Sciences, 2022)
Background: The movement control order (MCO) implemented during the COVID-19 pandemic has caused higher learning institutions to utilise online teaching otherwise known as emergency remote teaching (ERT). Besides the changing mode of teaching and learning, prospective stressors were found to affect students’ mental health. This study is aimed at evaluating the effect of ERT and associated stressors on mental health status and education among undergraduate students of UniKL-RCMP. Methods: A cross-sectional study was undertaken with data collection conducted from March to April 2021. An online questionnaire was delivered to all students of UniKL RCMP, using the snowball method. The number of students who responded was 307. The data was analysed using SPSS version 21. Results: Out of 307 respondents, anxiety (68.7%), stress (41.4%), and depression (55.7%), ranging from mild to severe, were found to occur among the undergraduates. Prospective stressors which include living conditions, Internet accessibility and sleeping hours, predominantly affect undergraduate mental health problems. The negative impact of ERT was found to be on decrease in level of attentiveness (51.5%) and assessment grades or marks (37.8%). Students disagreed (58.3%) that completing the course virtually is more effective than face-to-face learning while 45.9% of them felt that they have lagged in their education. Conclusion: ERT with some stressors were reported to have caused drawbacks in education and gave rise to mental health issues among students during the COVID-19 pandemic.